Examination of the optimum use of UV lacquers and inks in the offset printing - (:unkn) unknown (Chemical Publishing Co., 2012)
UV products were introduced more than 30 years ago. During the following years, technology has gone through a metamorphosis resulting in significant improvements. UV technology offers an alternate compliance strategy to the problem of volatile organic compounds. Ink ands lacquers dried with UV curing are preferred to their rapid drying, brightness, frictional strength and high stacking characteristics. System has become preferred more than conventional-dried systems due to opportunities in investment, equipment, ink saving, printing on various material surfaces, higher quality, more rapid printing and high stacking.
Keywords: Offset printing; UV curing; UV ink